Dynamics of Contestment of Formal and Informal Institutions in The Public Space in Governance of the Brantas River Watershed Area - Ulfa Binada (Policy & Governance Review, 2023)
This research focuses on the dynamics of formal and informal institutions in their contestation in the Brantas Watershed (DAS). As a public space, the Brantas Watershed is of concern to the government and an informal organization, Ecoton. The presence of Ecoton in the management of the Brantas Watershed was triggered because the government program was only ceremonial and considered unsustainable. This research uses a qualitative approach with a soft system methodology (SSM). In the data collection process, this study used the focus group discussion (FGD) method as primary data and a literature study as secondary data. Furthermore, this research uses the structure-culture-process (SKP) theory and models of formal and informal institutional relations. The results of this study indicate that relationships have been successfully formed through the contestation of formal and informal institutions in the public space. The Brantas River Basin Center (BBWS) and the Environmental Service (DLH), as representatives of the state that have a formal power base, are not sufficiently capable of managing the Brantas DAS optimally. This is due to the complexity and breadth of the Brantas watershed area in East Java, thus triggering the presence of the informal Ecoton institution. The presence of Ecoton in the governance of the Brantas Watershed is a force that supports and complements the government, but at the same time, Ecoton can be a government competitor and even a substitute in the public sphere. The contestation of these formal and informal institutions is part of social integration and collaborative governance.